Phase relations and Pt solubility in sulphide melt in the FE-NI-CU-S system at 1 ATM : implications for evulution of sulphide magma in the Merensky reef, Bushveld Complex, South Africa - Theron, Luhann Marlon (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.